A novel method for the assessment of targeted PEI-based nanoparticle binding based on a static surface plasmon resonance system - Hoebel, Sabrina; Vornicescu, Doru; Bauer, Marius; Fischer, Dagmar; Keusgen, Michael; Aigner, Achim (Analytical Chemistry, 2014)
The delivery of nucleic acids is a major hurdle in gene therapy or therapeutic gene knockdown, and the development of intelligent and safe nanoparticles as carrier systems is thus under intense investigation. The introduction of ligands for their targeted delivery is of major interest. Here, we describe a novel approach for the analysis of the binding properties of antibody-functionalized nanoparticles, using surface plasmon resonance (SPR) in a static cuvette system. By chemical coupling of the Epidermal Growth Factor Receptor (EGFR)-specific antibody cetuximab to poly(ethylene imine) (PEI) via a PEG-spacer and subsequent DNA or siRNA complexation, we generated targeted nanoplexes with low surface charge. Antibody-mediated uptake into EGFR overexpressing cells was observed. SPR measurements with use of a novel, protein A-based sandwich system for the immobilization of the target receptor in its correct steric orientation allowed the analysis of the specific PEI-PEG-cetuximab binding to EGFR and the determination of binding affinities. Importantly, our cuvette-based SPR assay system was also suitable for the monitoring of ligand-mediated nanoparticle binding, without convection or shear stress. We conclude that our SPR sandwich system allows the precise analysis of the binding of ligand-functionalized nanoparticles in real-time, and we thus establish SPR for the in vitro evaluation of ligand modifications for generating targeted nanoparticles. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2020-10-13